Hemi-central retinal artery occlusion in young adults - Rishi Pukhraj; Rishi Ekta; Sharma Tarun; Mahajan Sheshadri (Indian Journal of Ophthalmology, 2010)
Amongst the clinical presentations of retinal artery occlusion, hemi-central retinal artery occlusion (Hemi-CRAO) is rarely described. This case series of four adults aged between 22 and 36 years attempts to describe the clinical profile, etiology and management of Hemi-CRAO. Case 1 had an artificial mitral valve implant. Polycythemia and malignant hypertension were noted in Case 2. The third patient had Leiden mutation while the fourth patient had Eisenmenger′s syndrome. Clinical examination and fundus fluorescein angiography revealed a bifurcated central retinal artery at emergence from the optic nerve head, in all cases. Color Doppler examination of the central retinal artery confirmed branching of the artery behind the lamina cribrosa. It is hypothesized that bifurcation of central retinal artery behind the lamina cribrosa may predispose these hemi-trunks to develop an acute occlusion if associated with underlying risk factors. The prognosis depends upon arterial recanalisation and etiology of the thromboembolic event.